Controlled Synthesis of Highly Crystallized Mesoporous Mn2O3 and Mn3O4 by Using Anionic Surfactants. Issue 5 (21st January 2016) - Jothi, Palani Raja; Pramanik, Malay; Li, Cuiling; Kannan, Shanthi; Malgras, Victor; Salunkhe, Rahul R.; Yamauchi, Yusuke
Abstract: Mesostructured manganese oxide (Mn3 O4 ) is prepared by a soft‐templating method employing sodium dodecyl sulfate (SDS) as a structure‐directing agent. By removing the template from the as‐prepared mesostructured Mn3 O4 by extraction or calcination, we successfully synthesized highly crystallized mesoporous Mn3 O4 or Mn2 O3, respectively, with different crystalline structures. Abstract : Finding an agent : The synthesis of mesoporous manganese oxides ( meso‐ Mn2 O3 and meso ‐Mn3 O4 ) with crystalline framework by using sodium dodecyl sulfate (SDS) as a structure directing agent is reported. The superior electrocatalytic activity of the materials towards oxygen reduction reaction (ORR) has been tested.